Outcomes of women at high familial risk for breast cancer: An 8‐year single‐center experience. Issue 2 (28th October 2019) - Lammert, Jacqueline; Skandarajah, Anita R.; Shackleton, Kylie; Calder, Patricia; Thomas, Susan; Lindeman, Geoffrey J.; Mann, Gregory Bruce
Abstract: Objectives: The value of a high‐risk surveillance program for mutation carriers and women at high familial breast cancer risk has not been extensively studied. A Breast and Ovarian Cancer Risk Management Clinic (BOCRMC) was established at the Royal Melbourne Hospital in 2010 to provide multimodality screening and risk management strategies for this group of women. The aims of this study were to evaluate the program and describe breast cancer diagnoses for BRCA1, BRCA2, and other germline mutation carriers as well as high‐risk noncarriers attending the BOCRMC. Methods: Clinical data from mutation carriers and noncarriers with a ≥25% lifetime risk of developing breast cancer who attended between 2010 and 2018 were extracted from clinic records and compared. The pattern and mode of detection of cancer were determined. Results: A total of 206 mutation carriers and 305 noncarriers attended the BOCRMC and underwent screening on at least one occasion. Median age was 37 years. After a median follow‐up of 34 months, 15 (seven invasive) breast cancers were identified in mutation carriers, with seven (six invasive) breast cancers identified in noncarriers. Of these, 20 (90.9%) were detected by annual screening, whereas two (9.1%) were detected as interval cancers (both in BRCA1 mutation carriers). Median size of the invasive breast cancers was 11 mm (range: 1.5‐30 mm). The majority (76.9%) were axillary node negative. In women aged 25‐49 years, the annualized cancer incidence was 1.6% in BRCA1, 1.4% in BRCA2 mutation carriers, and 0.5% in noncarriers. This compares to 0.06% annualized cancer incidence in the general Australian population. Conclusions: Screening was effective at detecting early‐stage cancers. The incidence of events in young noncarriers was substantially higher than in the general population. This potentially justifies ongoing management through a specialty clinic, although further research to better personalize risk assessment in noncarriers is required.